The Inscription of Tiberius Claudius Claudianus Hetereianus Engraved on a Marble Column Found in the ‘Saranda Kolones’ Castle at Nea Paphos, Cyprus - Kordas, Anna Urszula (Études et Travaux, 2023)
This paper offers the editio princeps of a Greek inscription engraved on a marble column discovered in the ‘Saranda Kolones’ Castle at Nea Paphos in Cyprus. The inscription, dated to the second or early third century AD, contains the names of the otherwise unknown Tiberius Claudius Claudianus Hetereianus, a member of the ordo equester, a founder of the column. This is the only known inscription mentioning the name Hetereianus. It remains an open question as to whether the man mentioned by the inscription was a Cypriot by birth or came to Cyprus, as well as whether he was the founder of this column only or a whole colonnade.